DINAMIKA EKONOMI INFORMAL: STUDI KASUS PEDAGANG PASAR TRADISIONAL DI KOTA X - M. Udayan (PT. Habe Cendekia Utama, 2025)
The informal economy in Indonesia is a significant sector, where workers lack formal legal protection and work independently or with the assistance of casual laborers. This study aims to understand the dynamics of the informal economy of traditional market traders in City Surabaya, providing academic, practical, and public policy implications. This study uses a descriptive-qualitative approach to understand the dynamics, patterns, social networks, and factors in traditional markets. The sample size was 100-200 respondents, with 15-30 key informants including senior traders, market managers, supplier representatives, and regular customers. The research shows that the informal economy in Indonesia, dominated by micro and small enterprises, plays a significant role in absorbing more than 59% of the workforce by 2025. Informal enterprises rely on equity, social loans, and trust networks as their primary social capital. The informal economy and traditional markets are crucial to the local and national economy. The informal economy is characterized by flexible micro and small enterprises, relying on limited capital and social networks, and contributing significantly to employment.